2009
DOI: 10.1097/wnr.0b013e328332c4f4
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal versus foveal N400s dissociate spreading activation from contextual fit

Abstract: Using concurrent electroencephalogram and eye movement measures to track natural reading, this study shows that N400 effects reflecting predictability are dissociable from those owing to spreading activation. In comparing predicted sentence endings with related and unrelated unpredicted endings in antonym constructions ('the opposite of black is white/yellow/nice'), fixation-related potentials at the critical word revealed a predictability-based N400 effect (unpredicted vs. predicted words). By contrast, event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
71
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 23 publications
15
71
1
Order By: Relevance
“…Previous studies using a similar task resulted in mixed results (Baccino and Manunta, 2005;Simola, Holmqvist, & Lindgren, 2009), however they only analyzed the early latencies previous to the N400 component. Our results are consistent with data obtained in sentence reading with the flanker-word RSVP paradigm (Barber et al, 2010(Barber et al, , 2012(Barber et al, , 2013Li et al, 2015) and with one FRP experiment that reported parafoveal N400 effects during sentence reading (Kretzschmar et al, 2009). Even when the ERPs showed a clear parafovea-on-fovea effect, EM measures in the present experiment were not sensitive to our experimental manipulation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies using a similar task resulted in mixed results (Baccino and Manunta, 2005;Simola, Holmqvist, & Lindgren, 2009), however they only analyzed the early latencies previous to the N400 component. Our results are consistent with data obtained in sentence reading with the flanker-word RSVP paradigm (Barber et al, 2010(Barber et al, , 2012(Barber et al, , 2013Li et al, 2015) and with one FRP experiment that reported parafoveal N400 effects during sentence reading (Kretzschmar et al, 2009). Even when the ERPs showed a clear parafovea-on-fovea effect, EM measures in the present experiment were not sensitive to our experimental manipulation.…”
Section: Discussionsupporting
confidence: 82%
“…To sum up, whereas with EM data parafovea-on-fovea effects and preview semantic effects have not been firmly established (Schotter et al, 2012), ERPs have shown these effects using a paradigm that prevents eye movements and displays the stimuli with constant presentation times (Barber et al, 2010(Barber et al, , 2012(Barber et al, , 2013Li et al, 2015). Co-registration of EEG and EM has also led to mixed results, with some studies reporting parafovea-on-fovea effects (Baccino & Manunta;Kretzschmar et al, 2009) and others that do not (Simola et al, 2009;Dimigen et al 2011Dimigen et al , 2012). …”
Section: Introductionmentioning
confidence: 99%
“…When the sentences were presented for natural reading, the ERPs time-locked to fixation on the target word also revealed a robust predictability effect that was again highly similar in amplitude and scalp distribution to the N400 during SVP. Importantly, relative to SVP the onset of the N400 in natural reading was advanced by more than 100 ms, a result that is reminiscent of the findings by Kretzschmar et al (2009) with semantic anomalies. Moreoever, with the boundary paradigm, which denies preview to the upcoming word by masking we could demonstrate that the early onset of the N400 in natural reading is in fact due to the parafoveal information available in natural reading (Dimigen et al, 2008).…”
Section: Co-registration Of Ems and Eegsupporting
confidence: 52%
“…In a later study, Kretzschmar, Bornkessel-Schlesewsky, and Schlesewsky (2009) used the same sentence material, but had subjects read the sentences during normal left-to-right reading while they collected both EEG and EMs. To avoid eye movement artifacts, Kretzschmar et al constrained the analysis to electrodes close to the vertex, which are not strongly influenced by horizontal saccades.…”
Section: Co-registration Of Ems and Eegmentioning
confidence: 99%
“…Certainly, even with a normal presentation rate, the RSVP procedure remains artificial and can only approximate natural reading where subjects move their eyes freely across sentences at their own pace (cf., Ditman et al, 2007;Nieuwland & Van Berkum, 2006 ; see also Baccino & Manunta, 2005;Dimigen et al, 2009;Dimigen, Kliegl, & Sommer, in press;Hutzler, Braun, Vo, Engl, Hofmann, Dambacher et al, 2007;Kretzschmar, Bornkessel-Schlesewsky, & Schlesewsky, 2009;Kliegl et al, 2012;Simola, Holmqvist, & Lindgren, 2009). There is reason to believe that this technique has the potential to provide novel insights not only into the timeline of word recognition but into visual perception in general.…”
Section: Discussionmentioning
confidence: 99%